Paleoenvironment of Tanjung Formation Barito Basin- Central Kalimantan Based on palynological data - Winantris Winantris; Helman Hamdani; Ellin Harlia (UIR PRESS, 2017)
The research area is located in the Muara Teweh, North Barito, Central Kalimantan. The cocking coal deposits are well known as they were produced from this area. Upper part of Tanjung Formation is target coal production. The study objectives are to analyze paleoenvironment and to determine the relative age of coal deposits based on palynological data. Preparing palinological analysis used standard procedure by hydrofluoric acid method.Palynomorphs data grouped into six types of ecology, and the sequence is as follows ; fresh water and lowland (41,75 %), brackish water swamp (30,10%), Peat and freshwater swamp (17,96%), marine element (7,77 %), back mangrove (1,46%) and upland element (0,97). Palmae pollen is very dominant, especially from freshwater and peat swamp that grow around coastal area i.e. Dicolcopollis, Proxapertites cursus, Proxapertites operculatus, Longapertites and Palmaepollenites kutchensis. Although marine fossil found, but the frequency less than one percent, that was the evidence of influence sea water to swamp area. The palynomorphs indicate the coal sedimented at upper delta plain. Fossil index of relative age consist of Proxapertites cursus, Proxapertites operculatus, Magnastriatites howardi Verrucatosporites usmensis, Retistephanocolpites , and Ixonantes type which refer to Late Eocene.